(3GdTLQ hGdKeQs - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s ((3bGSe Hf eMeO QVG GdZQGhjs)
(3ChdgG (B:s
{(3Bde ZdHJ GdQhe aj COfi GdCQV hge ef HYO ZdHge SjZdHhf(B...}...(3OhdI GdESdGe OhdI GdCJQGc(B... (3CMSf GdOhd(B...(3HYO GdUMGHI(B...s
(3BNQgG (B:s
(3hjQLY Gdeje GdeSJbje Edi HGH ehdGg hSOI ef JhdGg(B...s
(3efShNI Yf fSNI GdCUds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B531s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMQha hGdChaGbs